Effects of recovery mode on physiological and psychological responses and performance of specific skills in young soccer players - Gharbi, A.; Masmoudi, L.; Chtourou, H.; Chaari, N.; Tabka, Z. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The ability to perform repeated sprints is likely influenced by the mode of the recovery. Despite performance time, peak power, and mean power measured in most of studies, there are other specific sport abilities that should be examined after different recovery strategies.The aim of this study was to examine the effects of recovery modes (active [AR] vs. passive [PR]) on physiological performance (lactate, HR, and blood pressure), psychological performance (perceived exertion rating [RPE] and feeling scale [FS]), and specific skills (kicking accuracy [KA] and repeated dribbling) in young soccer players.